Comparative Study of Microwave Oven-Assisted Tissue Processing with Isopropanol and Mineral Oil Mixture and Propylene Glycol Methyl Ether on Morphological Quality of Tissue Sections - Darsheny, Sri; Nway Aye, Saint; Krishnappa, Purushotham; Ravindran, Rashindra (IIUM Medical Journal Malaysia, 2021)
Background: Over several years, xylene has been traditionally utilised as the clearing agent of choice in tissue-processing due to effectiveness in rapidly clearing tissue, facilitating the paraffin infiltration process. However, xylene use adversely impacts the health of personnel with long term exposure due to toxicity. In order to overcome these effects and replace it with a safer alternative agent, the present study aims to compare quality of tissue sections processed using an isopropanol and mineral oil mixture and propylene glycol methyl ether (PGME) as xylene substitutes. Methods: Rat skeletal muscle tissue samples (n=20) were prepared for each processing protocol with xylene substitutes. Tissue specimens were processed according to the proposed microwave protocol. The clearing steps were performed using isopropanol and mineral oil mixture, and PGME, replacing xylene. From each paraffin-embedded block, one section of 4-5µm thickness tissue was obtained and conventionally-stained with Haematoxylin and Eosin (H&E). The histological sections were microscopically assessed and scored by a pathologist. A qualitative analysis was performed with the results obtained. Results: The overall score obtained for xylene processed tissue was 100% with a score of 2 for all the 3 parameters assessed. However, the outcome for tissue processed with isopropanol and mineral oil mixture was 28.6% unsatisfactory, 28.6% satisfactory and 42.8% good. In PGME-treated tissues, 14.3% were unsatisfactory sections, 71.4% were satisfactory and 14.3% produced good quality sections. Overall, tissues processed using both substitutes exhibited sufficient staining quality in terms of the aforementioned parameters as compared to xylene-processed tissues, though significant difference in scores were observed. Conclusion: Despite several challenges faced in the study, isopropanol and mineral oil mixture and PGME can be suggested as alternative clearing agents to xylene, provided having access to a more sophisticated microwave oven with precise temperature control for complete tissue-processing.